Fuel measurement method on a river boat (2006)
A way of improving the method of measuring fuel in a river boat, specifically in a tugboat, is discussed. The reference framework on which this article is based is the strategy used to establish the amount of fuel present in the vessels of the vessel. The method that has been used so far, produces an error influenced by perturbation factors, such as the tilt and the way of tugging the tug. It was sought to develop an alternative method that would reduce the error between the fuel delivered and that measured on the boat. This new method managed to be independent of the inclination without using an inclinometer or angle measuring instrument.